2016
DOI: 10.2508/chikusan.87.219
|View full text |Cite
|
Sign up to set email alerts
|

Estimating chromosomal genetic diversity of Kuchinoshima feral cattle using high density SNP chip

Abstract: Kuchinoshima cattle are unique feral cattle in Kuchinoshima Island in Kagoshima prefecture. We genotyped 54K SNPs for Kuchinoshima cattle, Japanese Black, Japanese Brown and Japanese Holstein using high density SNP chip to estimate genetic diversity and genetic structure in Kuchinoshima cattle.Average minor allele frequency in Kuchinoshima cattle was lower (0.089) than those of the other populations (0.181-0.251). Ratio of monomorphic SNPs for each chromosome in Kuchinoshima cattle ranged from 47.7% (BTA24) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Siqin et al (2014) reported that four out of six functional gene variants (NCAPG, FASN, SCD, SREBP-1, F11 and MC1R) were monomorphic in 32 Kuchinoshima cattle. Saito et al (2016) genotyped 54 K single nucleotide polymorphisms in Kuchinoshima, Japanese Black, Japanese Brown and Japanese Holstein cattle, and found that the average minor allele frequency in Kuchinoshima cattle was lower (0.089) than in other populations (0.181-0.251). These results also indicate the extremely low genetic diversity of Kuchinoshima cattle, which may be explained by a founder effect and/or genetic drift in the small population (< 100 animals) that has survived on Kuchinoshima Island for many generations.…”
Section: Discussionmentioning
confidence: 99%
“…Siqin et al (2014) reported that four out of six functional gene variants (NCAPG, FASN, SCD, SREBP-1, F11 and MC1R) were monomorphic in 32 Kuchinoshima cattle. Saito et al (2016) genotyped 54 K single nucleotide polymorphisms in Kuchinoshima, Japanese Black, Japanese Brown and Japanese Holstein cattle, and found that the average minor allele frequency in Kuchinoshima cattle was lower (0.089) than in other populations (0.181-0.251). These results also indicate the extremely low genetic diversity of Kuchinoshima cattle, which may be explained by a founder effect and/or genetic drift in the small population (< 100 animals) that has survived on Kuchinoshima Island for many generations.…”
Section: Discussionmentioning
confidence: 99%
“…From our previous studies (Mannen et al, 2017;Saito et al, 2016), the Kuchinoshima cattle have quite low genetic diversity. By the mtDNA analysis, 32 Kuchinoshima cattle have only an identical haplotype belonged to haplogroup T3.…”
Section: Genetic Diversity Of Kuchinoshima Feral Cattlementioning
confidence: 94%
“…By the mtDNA analysis, 32 Kuchinoshima cattle have only an identical haplotype belonged to haplogroup T3. In addition, we genotyped 54K SNPs for Kuchinoshima cattle to estimate genetic diversity and genetic structure in Kuchinoshima cattle (Saito et al, 2016). The average minor allele frequency in Kuchinoshima cattle was quite lower (0.089) than those of the other populations of Japanese Black, Japanese Brown and Japanese Holstein (0.181 -0.251).…”
Section: Genetic Diversity Of Kuchinoshima Feral Cattlementioning
confidence: 99%